Applying modularity in product design and in production: an analysis at a truck and bus manufacturer - Rodrigues, Edilson Alves; Carnevalli, José Antonio; Miguel, Paulo Augusto Cauchick (Revista Gestão da Produção Operações e Sistemas, 2012)
The aim of this paper is to investigate modularity application in terms of design and production. This work describes a case study conducted in a commercial vehicles assembler that uses a distinct productive organization. It also presents the relations with suppliers with the assembler, the changes in the production system due to the launching of a new heavy vehicle and the initiative of implementing a pilot plant to be used in new product development. The paper compares the results with the literature by emphasizing the relationship between the assembler and suppliers, the development of new products and modular production. The main conclusions confirm the best practices pointed out by the literature about the modular consortia as well as highlight the relation between modularity in design and in production.Keywords: modular consortia; Modularity; Modular Design; Supply Chain.